Cervical cancer: a hospital based KAP study among women aged 18 years and above in Northern India - Gupta, Rajiv Kumar; Singh, Parveen; Langer, Bhavna; Kumari, Rashmi; Sharma, Pawan; Gupta, Riya (International Journal Of Community Medicine And Public Health, 2019)
Background: Cervical cancer is known for its late detection due to a variety of reasons chiefly lack of knowledge, undesirable attitudes and poor practices. Early screening and adequate knowledge about the disease remains the important safe guards against this disease. The study aimed to assess the knowledge, attitudes and practices of the women aged 18 years and above regarding cervical cancer visiting a tertiary care teaching hospital. Methods: The present cross sectional hospital based study was conducted in Jammu city, Jammu and Kashmir, India. All the women aged 18 years and above visiting OPD of gynaecology-obstetrics department of Government Medical College Jammu and willing to participate were administered a pretested questionnaire to collect the relevant data. Results: It was found that 91.56% of the respondents had heard of cervical cancer with 83% reporting that it was both preventable as well as curable. Multiple sex partners were the most important risk factor identified. Among the attitudes, 62% agreed that screening was harmless to the client. Only one third knew about the availability of preventive vaccine. About 83.6% of them had never been screened by Pap smear. However willingness to get HPV vaccination was found to be high. Conclusions: Though knowledge among the respondents was found to be adequate but it lacked transformation into attitudes and practices. In this connection, authors recommend health promotion campaigns to educate women and the community about cervical cancer and its preventability through screening.